Determinants of stunting and severe stunting among under-fives: evidence from the 2011 Nepal Demographic and Health Survey. - Tiwari, Rina.; Ausman, Lynne M.; Agho, Kingsley Emwinyore. (2016)
Background: Stunting remains a major public health concern in Nepal as it increases the risk of illness, irreversible body damage and mortality in children. Public health planners can reshape and redesign new interventions to reduce stunting and severe stunting among children aged less than 5 years in this country by examining their determinants. Hence, this study identifies factors associated with stunting and severe stunting among children aged less than five years in Nepal.; Springer Open.